The association between hearing loss and depression in the China health and retirement longitudinal study - Yanju Zhang; Xiaofang He; Yibo Liu; Chunhong Tian; Hui Yang; Lin Zhang (Scientific Reports)
Abstract Hearing loss (HL) is a common health issue among older adults worldwide, and its incidence is expected to increase as the population ages. A study has shown that among the estimated 500 million people with hearing impairments worldwide, 28 million Americans suffer from hearing disabilities, and the highest number of individuals with hearing impairments is found in the 45-to-64 years old age group. Depression is a significant public health concern for middle-aged and older adults. In 2015, researchers used data from over 100,000 participants that were collected by the UK Biobank to perform a cross-sectional study and reported that the association between hearing impairment and depression was more pronounced among younger participants (aged 40–49 years) and among those with milder forms of depression. These findings suggest that the impact of hearing impairment on mental health may begin to emerge in middle age. Hearing loss may lead to more obstacles for middle-aged individuals in terms of work and social interactions, thereby increasing the risk of depression. Early intervention for hearing impairment is particularly important for middle-aged people, as it can help identify early risk factors and provide more effective interventions to improve mental health and quality of life. Therefore, building on the existing literature that predominantly focused on older adults, this study involved analysing data from the China Health and Retirement Longitudinal Study(CHARLS) database, expanding the age range to 45 years, to investigate the relationship between self-reported hearing loss and depression among middle-aged and older adults. This research used data from the 2018 China Health and Retirement Longitudinal Study (CHARLS), including data from 5207 individuals aged 45 years and older. Hearing status was self-reported by the participants, whereas depression was assessed with the 10-item Center for Epidemiologic Studies Depression Scale (CES-D-10). A multivariable logistic regression model was used to investigate the association between self-reported hearing loss and depression, controlling for sociodemographic variables that are associated with depression in middle-aged and older populations. This study involved the use of a multinomial logistic regression model to analyse the relationship between self-reported hearing loss and depression among middle-aged and older adults, with adjustments made for potential confounding variables. The analysis revealed significant relationships between depression and factors such as hearing status, sex, place of residence, self-rated health, chronic diseases, disabilities with respect to activities of daily living (ADLs), and satisfaction with life. Specifically, individuals with self-reported hearing loss, female individuals, individuals residing in rural areas, individuals with poor self-rated health, individuals with chronic diseases, and individuals with disabilities related to ADLs were more likely to experience depression. In the unadjusted model that was used to analyse the relationship between self-reported hearing loss and depression among middle-aged and older adults, both fair hearing (unadjusted OR = 1.556, 95% CI 1.377–1.758) and poor hearing (unadjusted OR = 2.001, 95% CI 1.630–2.457) were significantly associated with the prevalence of depression. After controlling for various covariates, including sex, age, residential status, education level, marital status, health status, physical disability, chronic diseases, activities of daily living (ADLs), and satisfaction with life, our study revealed that both fair hearing (adjusted OR = 1.235, 95% CI: 1.078, 1.415) and poor hearing (adjusted OR = 1.335, 95% CI: 1.063, 1.677) remained significantly correlated with the prevalence of depression among middle-aged and older adults. Previous research has focused primarily on older adults. Therefore, the present study expanded the age range to include individuals as young as 45 years old. The results show that fair hearing and poor hearing are significantly associated with the prevalence of depression among middle-aged and older adults. These findings suggest that self-reported hearing loss is a risk factor for depression in this population in China. The association between self-reported hearing loss and depression is not limited to older adults but also includes middle-aged individuals.